Improving The Ability to Perform Summary Calculation Operations Using Number Bag Media - Tri Wahyuni, Endah; Subiyantoro, Singgih; Suparti (Edutech Publishing Media, 2023)
Meaningful learning begins with active student participation in educational activities. However, learning often remains teacher-centered due to limitations in the use of teaching aids, resulting in low student engagement when solving problems. This study aims to improve first-grade students’ ability to solve addition problems in mathematics by applying number pocket media at SD Negeri Godog 1. The research employed Classroom Action Research using the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection at the end of each cycle. The research subjects were 15 first-grade students at SD Negeri Godog 1, Polokarto. Data were collected through observation, testing, and documentation. The results show that student learning outcomes in mathematics, specifically in addition, can be improved through the use of number pocket media. This is evident from the increase in student learning outcomes from seventy-three percent in the first cycle to ninety-three percent in the second cycle. This improvement indicates that the success indicators set in this study were achieved. Therefore, it can be concluded that the use of number pocket media has a significant positive impact on first-grade students mathematics learning outcomes in addition material. Furthermore, the study contributed not only to enhancing students mathematical abilities but also to improving teachers creativity in delivering engaging lessons.